"Con benedicente affetto": Ventuno lettere inedite di Clemente Rebora - Gadaleta, Ludovico Maria (Rivista di storia della Chiesa in Italia, 2020)
These unpublished letters of Clemente Rebora have been found in almost their entirety in the Rosminian Archives in Stresa. Belonging to the period following Rebora’s conversion, they reveal his priestly soul, even regarding mostly ordinary subjects, and his most authentic dimension. It is confirmed, therefore, the necessity of a unitarian view about Rebora’s life and literary production: there are no such things as ‘before’ and ‘after’ his conversion, but two faces of the same human and poetical experience.